Cochlear Reimplant Rates in Children: Twenty‐Year Experience in a Quaternary Pediatric Cochlear Implant Center. (23rd August 2013) - Trozzi, Marilena; Sharp, James; Toma, Shamim; Powell, Harry; Broxholme, Catherine; Jephson, Christopher G.; Cochrane, Lesley‐Ann
Abstract : Objectives: Determine the incidence and risk factors for cochlear re‐implantation in children. Methods: Retrospective case review in a quaternary pediatric cochlear implant (CI) center. Subjects studied: Pediatric CI patients requiring cochlear re‐implantation. Interventions: Cochlear explantation/re‐implantation. Outcome measures: Etiology and timing of device re‐implantation, risk factors for revision surgery. Independent variables: patient age, side, surgeon, etiology of deafness, co‐morbidities, CI manufacturer, incidence of re‐implantation, timing of re‐implantation. Results: Seven hundred and fifty‐two pediatric cochlear implants were performed in 619 children between 1993 and 2013. 37 patients underwent 39 explanation/re‐implantation procedures (5.2%). The most common reason for explantation/re‐implantation was device failure in 21 (2.8%). Risk factors for device failure were preceding head trauma and known manufacturing defect/recalled device. Medical/surgical issues accounted for 18 (2.4%) re‐implantations and changed over the study period. The mean time to re‐implantation surgery was 4 years. Etiology of deafness did not correlate with the need for revision surgery. Conclusions: The incidence of re‐implantation in our pediatric cochlear implant population is comparable to other published studies. However the etiology of deafness, in particular meningitis, does not appear to increase the risk of failure as described in previous series. The most common reason for re‐implantation remains device failure.